Fenomena Sound Horeg: Kajian Hukum Islam dan Hukum Positif Indonesia terhadap Kebisingan Pengeras Suara Ekstrem - Fatma, Fitrotul Maulida (Maliki Interdisciplinary Journal, 2025)
The phenomenon of sound horeg, namely the use of vehicles equipped with high-powered sound systems that generate extreme noise, has become an increasingly widespread social issue in various regions of Indonesia. For some communities, this practice is perceived as a form of entertainment or cultural expression. However, its presence causes significant negative impacts, including health problems such as hearing loss and increased stress, social unrest, and violations of public order. From an Islamic perspective, several scholars, including the Indonesian Ulema Council (MUI) and the East Java MUI, have declared that the use of sound horeg is prohibited (haram). This argument is based on fiqh principles that emphasize the prohibition of harm (mudarat), wasteful behavior (tabdzir), and activities that provide no benefit compared to the damage caused. Meanwhile, under Indonesian positive law, the practice of sound horeg violates noise regulations, including Minister of Environment Decree No. 48 of 1996, Law No. 32 of 2009 on Environmental Protection and Management, and Government Regulation No. 41 of 1999 on Air Pollution Control. Such violations may result in administrative sanctions or criminal penalties, including fines and imprisonment. This article employs a normative qualitative approach (library research) to examine both Islamic law and Indonesian legal regulations, and to provide policy recommendations for controlling this phenomenon.